Clash of the Generations - Grubb, Valerie (Ascent Audio, 2019)
Case studies and strategies for more effective multi-generational management Clash of the Generations explores this new and increasingly common workplace phenomenon, and provides strategies to help managers navigate this ever more complex maze. Traditionally, older workers would retire and make room for the next generation; instead, Baby Boomers are now prolonging their time in the workplace, yet the successive generations are still coming in. Senior leaders are now left to manage a blended workplace comprised of up to four generations-each with their own ideas of work ethic, work/life balance, long-term career goals, and much more. Management is challenging at the best of times, but the new prevalence of generation gaps-sometimes even layered-add an entirely new dimension to an already complex responsibility. This book presents case studies and interviews with representatives of companies with age-diverse workforces, detailing innovative strategies for smoothing out the bumps and helping everyone work together. Managers have long wished that their positions came with an instruction manual, and this book delivers with a host of effective inter-generational management strategies illustrated by real-world companies.
Online resource; Title from title page (viewed November 19, 2019)
Keywords: Business; Affaires; Audiobooks